Legalitas Hak Asuh Anak Dibawah Umur (Hadhanah) Akibat Perceraian Orang Tua Studi Kajian Tafsir Tematik - M. Rafi’i Anwar; Lilik Andar Yuni (Bulletin of Community Engagement, 2024)
For a child, divorce will definitely have quite a big impact. Especially if a child is still a minor, of course both parents must provide attention and guidance. Compilation of Islamic Law which regulates child custody rights given to the biological father and biological mother after divorce, Article 105 states that the biological mother has custody of children under the age of 12 years. However, in the divorce process there are often differences of opinion regarding whether or not the biological father should have custody of minor children. This research uses the maudhu'i (thematic) method to interpret the Koran. Researchers use the term tafsir maudhu'i to answer problems that exist in society. Tafsir Maudhu'i has the potential to produce new and accurate ideas from the Koran related to the issues discussed. This study was conducted from a normative perspective by looking at several recent cases relating to the legitimacy of parents to control custody of minor children after divorce based on applicable Indonesian positive law. Surah At-Tahrim verse 6 is the core of this research, because it states that people must take care of themselves and their families and educate their children.